Lexical acquisition in blended EFL learning: Integrating the enriched virtual model into VARK learning styles - Theresia Cicik Sophia Budiman; Sri Wuli Fitriati; Widhiyanto Widhiyanto (EduLite: Journal of English Education, Literature and Culture, 2026)
Vocabulary knowledge plays a fundamental role in second language (L2) proficiency and is strongly linked to students’ academic success in higher education. As blended learning becomes increasingly prevalent in university contexts, there is a growing need for instructional models that promote flexibility, learner engagement, and multimodal input. This study investigates the integration of VARK learning styles—Visual, Aural, Read/Write, and Kinesthetic—within the Enriched Virtual Model (EVM) to support lexical competence among English as a Foreign Language (EFL) learners. Adopting a mixed-methods design, the study involved 53 undergraduate students enrolled in a Lexical Studies course. Quantitative data were collected through pre- and post-tests to measure lexical gains, while qualitative insights were obtained from reflective journals and semi-structured interviews. Quantitative data were analyzed using paired-sample t-tests to examine pretest–posttest differences, one-way ANOVA to compare vocabulary gains across VARK learning-style groups, and Cohen’s d to determine effect size. Qualitative data were analyzed thematically following Braun and Clarke’s six-step framework.The findings reveal a statistically significant improvement in students’ lexical mastery, with a large effect size indicating a strong instructional impact. Analysis across VARK categories shows that Visual and Read/Write learners benefited most from the multimodal online materials, although positive progress was observed across all learning-style groups. Qualitative results further indicate that the VARK-informed EVM enhanced learner engagement, autonomy, and motivation by allowing students to interact with vocabulary through varied and flexible modalities. However, challenges related to cognitive workload and limited opportunities for kinesthetic engagement in online environments were also reported. These findings suggest the importance of balancing modality representation when designing blended vocabulary instruction. Overall, this study contributes to multimodal lexical pedagogy and offers practical implications for developing adaptive and learner-centered blended learning models in higher education.